The Modifying Effect of Strategic Intelligence in The Relationship Between Strategic Leadership and Organizational Agility: An Applied Study on Palestinian Universities - Alregeb, Tawfeeq Zayed Mohammad (Journal of Educational and Psychological Sciences, 2022)
This study aimed at analyzing the impact of Strategic Leadership on Organizational Agility through Strategic Intelligence at the Palestinian universities. To achieve the objectives of the study and test its hypotheses, the descriptive analytical method was used. The questionnaire was used as a main tool for data collection. The study sample consisted (analysis unit) of 182 leaders of academic leaders in Palestinian universities. The results of the study found that there was a significant impact of Strategic Leadership on Organizational Agility, there was a statistically significant impact of Strategic Leadership on Strategic Intelligence, there was a Significant impact of Strategic Intelligence on Organizational Agility, and there was an indirect impact of Strategic Intelligence as a moderating variable in the relationship between Leadership on Strategic and Organizational Agility. The study recommended the need to develop the skills and resources of Strategic Leadership among leaders in accordance with the main objectives of Palestinian Universities.
Keywords: Strategic Intelligence; Strategic Leadership; Organizational Agility; Academic Leaders; Palestinian universities